Clifford Geertz: Life among the Anthros – and other essays. (Fred Inglis, ed.). Princeton University Press 2010. 304 sider. ISBN 0691143587. Pris: 35,68. - Gaini, Firouz (Tidsskriftet Antropologi, 2011)
Intet resumé